Knowledge about the European Union in Political Education: What are the Effects of Motivational Predispositions and Cognitive Activation? - Weisseno, Georg; Landwehr, Barbara (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
This study investigates the effectiveness of political science classes in Germany. It analyzes whether or not 1,071 students in the 9th and 10th grade showed increases in knowledge after participating in the lesson series. This analysis focuses on the competence dimension “subject-specific content knowledge” as well as on the motivational predispositions “academic self-concept” and “interest in politics.” It also examines the instructional characteristics “inclusion of students” and “cognitive activation” from the students’ perspective. One’s academic self-concept and interest in politics, as well as cognitively activating instruction, have a moderately positive effect upon educational success. Social inclusion correlates with all constructs except subject-specific content knowledge.